2021
DOI: 10.3390/app112110167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Consumption in Fruit and Vegetable Processing Plants with the Use of Artificial Intelligence

Abstract: Fruit and vegetable processing has a significant impact on the environment due to its consumption of a significant amount of water. Water consumption mainly depends on the type of production and the technology used. Water in fruit and vegetable processing plants is used as a raw material, an energy carrier, and in hydro transport, as well as for washing raw materials and maintaining production hygiene. The variety of technological operations carried out in the production process and the seasonality of producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…They use 634 data to analyze the results of optimizing fruit and vegetable processing technology. The results obtained that the lowest water consumption will be achieved when the concentrate production is at a ratio of 2 to 1 for juices and beverages [57]. Computational and data processing capabilities using ML have also been used to increase vegetable yields [58].…”
Section: The Use Of Artificial Neural Network In Agricultural Plant G...mentioning
confidence: 99%
“…They use 634 data to analyze the results of optimizing fruit and vegetable processing technology. The results obtained that the lowest water consumption will be achieved when the concentrate production is at a ratio of 2 to 1 for juices and beverages [57]. Computational and data processing capabilities using ML have also been used to increase vegetable yields [58].…”
Section: The Use Of Artificial Neural Network In Agricultural Plant G...mentioning
confidence: 99%
“…It should be added that the results of the modeling of water consumption in fruit-and vegetable-processing plants by Trajer et al. [20] showed a definite impact of the production structure on the consumption.…”
Section: Water Consumptionmentioning
confidence: 99%
“…The problem affects in particular African countries, where the demand for water, energy and food resources is increasing and communities have limited availability and affordability in these areas [19]. Optimization of water consumption in fruit and vegetable processing was achieved with the use of genetic algorithms [20]. The results obtained allow for the appropriate selection of the production structure to ensure the lowest water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…It can result in project delays and increased construction costs in less severe cases, while in more severe cases, it can lead to well flooding and abandonment. Both research and engineering practice have consistently shown that water hazards have become the primary risk in the construction of deep well projects [5][6][7][8] . Therefore, improving the accuracy and reliability of engineering geological and hydrogeological investigations within the vertical shaft project area is a prerequisite for scientifically assessing water inflow risks and effectively managing water disaster.…”
Section: Introductionmentioning
confidence: 99%